The Subjective Deficit of Personal Potential and Personal Resources of Difficult Life Situations Overcoming - Bolshakova, Anastasiia (Psychological Prospects Journal, 2017)
The article deals with intercorrelation between subjective deficit of personal potential (personal realization) and personality resources of difficult life situations overcoming. The personal realization is defined as mental form of negative evaluation of self-realization process. It is reasonable, that this mental form is correlated with stagnation of self-accomplishment process and frustration of life success need during three life stages: past, present and future. Phenomenology of personal realization is described by: existential frustration, “loss of chance” feeling, negative evaluation of self-activity, low productiveness of life planning, pessimistic prognosis, feelings of spent potential, minor number of life tasks. “The Personal realization questionnaire” was used for diagnostics of subjective deficit of personal potential. The factor structure of new “Personal realization questionnaire” is suited for the study of three dimensions of personal realization: past, present and future. The scale “Present situation” describes minor saturation of present situation by important tasks, down level of activity, self-realization dissatisfaction. The scale “Perspective” describes pessimistic life-plans realization prognosis, feeling of spent personal potential, low productiveness of life planning, minor need of personal development. The scale “Retrospective” describes low level life-achievement, noneffectiveness of the past life planning, low level of activity, process and results of self-realization dissatisfaction. It is reasonable, that hardiness, tolerance for ambiguity, propensity to constructive strategies of coping behaviour belong to the personality resources of difficult life situations overcoming. A study of intercorrelation between personal realization and personal resources of difficult life situations overcoming is undertaken. It is found out, that the low level of personal realization is related to the hardiness, tolerance for ambiguity, constructive coping.